Governing Affective Citizenship : Denaturalization, Belonging, and Repression. - Beauchamps, Marie (Rowman & Littlefield International, 2018)
This book investigates politics of denaturalisation as a system of thought that influences seminal cultural political values, such as community, nationality, citizenship, selfhood and otherness.